Effectiveness of botanical pesticide combined with Beauveria bassiana on mortality, nutritional index and fecundity of Spodoptera litura L. - Tasafima Tesari; Amin Setyo Leksono; Irfan Mustafa (Cogent Food & Agriculture)
This study aimed to evaluate the effect of botanical pesticides mixed with entomopathogenic Beauveria bassiana on the growth and development of Spodoptera litura. This study adopted an experimental approach using a completely randomized design consisting of three treatments (botanical pesticides, B. bassiana, and a mixture of botanical pesticides and B. bassiana) and two control. The treatment and control had five concentration levels and were repeated four times. The test used the dip feed method. The relation between treatments and S. litura mortality was analyzed using probit analysis. Differences in means between treatment and control were analyzed using ANOVA. The results showed that both single and mixed treatments decreased relative consumption, inhibited relative growth rate and reduced fecundity of S. litura. The activity of the mixture of pesticides at the LC50 level has shown a synergistic effect. Thus, the mixture of botanical pesticides and B. bassiana could be developed as an alternative pesticide for sustainable biological control of S. litura.